Three new cryptic species of the genus Merodon Meigen (Diptera: Syrphidae) from the island of Lesvos (Greece) - Radenković, Snežana; Vujić, Ante; Ståhls, Gunilla; Pérez-Bañón, Celeste; Rojo, Santos; Petanidou, Theodora; Šimić, Smiljka (Zootaxa, 2011)
Descriptions are given of three new cryptic species of Merodon Meigen (Diptera: Syrphidae) from the island of Lesvos (Greece): Merodon latifemoris Radenković et Vujić n. sp. from the nigritarsis species group, Merodon pulveris Vujić et Radenković n. sp. from the natans species group and Merodon puniceus Vujić, Radenković et Pérez-Bañón n. sp. from the aureus species group. In addition to classical morphological characters, mitochondrial COI barcode sequences were generated for several specimens of each taxon.